Persepsi Pengunjung Terhadap Kualitas Makanan Di Cilalula Coffe Dan Eatery Pamulang - Asmawih; Yenny, Marya; Wahyuni, Nenny; Yaasir, Muhammad Hilmi (Politeknik Sahid, 2022)
Perception is a process by which individuals organize and interpret their sensory impressions to give meaning to their environment. Food is one of the basic needs in everyday life to support human life, maintain health, increase intelligence, and work productivity. Quality is not only found in services or goods but also food. The selection of raw materials is very influential in producing quality food. This study aims to determine how visitors perceive Cilalula Coffee & Eatery Pamulang. The sample used is a quota sampling technique obtained through consumers of Cilalula Coffee & Eatery Pamulang; the author examines consumers who came in January - June 2020; there are 2,668 data, with the data collection method using a questionnaire. This research is a case study using quantitative descriptive analysis. The sample used was 96 respondents from the entire population. Process the data using statistics with SPSS program tools; the results of data analysis from 9 indicators consisting of 27 quality statements of all statements that dominate food selection in each word.